Satisfaction of business students with the quality of classes during the pandemic: A mixed study in the Latin American context (2023)
Emergency remote education (ERD) adopted by universities amidst the COVID-19 pandemic has pursued to maintain students’ satisfaction. The current research inquiries into perception of the satisfaction towards the quality of classes during ERD. The research is carried out through a mixed sequential approach. Six focus groups in its qualitative phase, and 2074 students from the business undergraduate program in Colombia, Peru, and Mexico in its quantitative phase. Measure of satisfaction towards ERD establishes three dimensions: Concerns about academic quality, teaching strategies used by professors, and perceptions of access limitations. This study identifies a moderating effect of the perceptions of access limitations on the relationship of the teaching strategies and concerns about academic quality. In high constraints, =.-016, p < 0.0001, the relationship is weaker than medium constraints, = −0.22, p < 0.0001. In turn, the medium access limitation condition shows a weaker effect than the high limitation condition, = −0.28, p < 0.0001.